Analysis of the molecular and physiological effects following treatment with BC204 in Arabidopsis thaliana and Solanum lycopersicum - Loubser, Johannes (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.